Social futures, global visions (Blackwell, 1996)
Economic opportunity, civil society and political liberty. Palace fundamentalism and liberal democracy: oil, arms, and irrationality. The future of the State. The national question in Africa: internal imperatives. Positive aspects of community and the dangers of fragmentation...